Mechanics of agricultural materials - Sitkei, G. (University of Forestry and Wood Science, Sopron (Hungary). Dept. of Woodworking Machines) (Developments in Agricultural Engineering (Netherlands), 1986)
The importance of economical production of agricultural materials, especially crops and animal products serving as base materials for foodstuffs, and of their technological processing (mechanical operations, storage, handling etc.) is ever-increasing. During technological processes agricultural materials may be exposed to various mechanical, thermal, electrical, optical and acoustical (e.g. ultrasonic) effects. To ensure optimal design of such processes, the interactions between biological materials and the physical effects acting on them, as well as the general laws governing the same, must be known.The mechanics of agricultural materials, as a scientific discipline, is still being developed, and therefore has no exact methods as yet, in many cases. However, the methods developed so far can already be utilized successfully for designing and optimizing machines and technological processes.This present work is the first attempt to summarize the calculation methods developed in the main fields of agricultural mechanics, and to indicate the material laws involved on the basis of a unified approach, with all relevant physico-mechanical properties taken into account.The book deals with material properties, gives the necessary theoretical background for description of the mechanical behaviour of these materials including modern powerful calculation methods and finally discusses a large number of experimental results. Many of them can only be found in this book. Special attention is paid to the unified approach concerning theory and practice.The systematic treatment of the material makes the book useful to a wide circle of designers, researchers and students in the field of agricultural engineering. The book can also be used as a textbook at technical and agricultural universities.